ROAD MAP KEBISINGAN YANG DITIMBULKAN KENDARAAN BERMOTOR DI KOTA BOGOR (KAJIAN SEKSI II UNTUK KASUS DI DEPAN RSUD CIAWI BOGOR) - Syaiful, Syaiful; Rulhendri, Rulhendri (FSTPT Indonesia, 2015)
Motor vehicles always generate noise pollution levels are influenced by a variety of machine types and models of exhaust. Sound or noise pollution on the roads impassable formed due to the accumulation of noise sources, especially at a distance of buildings on these roads. Improved traffic flow from motorcycles, private cars, public transport passenger, and transportation of goods accounted for 53.65% of the noise level with a value of 53,810 dB noise.